Towards a “2nd Generation” of Quality Labels: a Proposal for the Evaluation of Territorial Quality Marks - Ramos, Eduardo; Universidad de Cordoba. España (2014)
Recent literature analyses the role of territorial specificities, as the core of territorial rural developmentstrategies based on differentiation. Unfortunately, the proliferation of quality assurance schemes is provokinga “labyrinth of labels” which diffuses the local efforts for capitalizing rural specificities. A second-generationof labels is currently being developed to simplify the territorial differentiation message. A number ofterritories in Southern Europe are basing their rural development strategies joining the so-called EuropeanTerritorial Quality Mark (ETQM) Project. This paper proposes an original methodology, designed anddeveloped by authors, for the evaluation of some of these second-generation labels. This methodology hasbeen validated in 15 rural territories as the pioneers of the ETQM in Spain.